Analisis Penerapan Akuntansi Manajemen Lingkungan dan Strategi Serta Inovasi Produk di Masa Pandemic Covid 19 (Studi Kasus Di Rumah Sakit Jiwa Dr. Radjiman Wediodiningrat) - Karina Wahyu Ariyanti; Nur Diana; Junaidi Junaidi (Universitas Islam Malang, 2023)
The objectives of this study are: (1) To find out the application of environmental management accounting and strategy and product innovation during the COVID-19 pandemic at the Dr. Radjiman Wediodiningrat Mental Hospital (2) To find out the obstacles in the application of environmental management accounting and strategies and product innovation during the covid 19 pandemic at the Dr. Radjiman Wediodiningrat Mental Hospital (3) To find out the solution to the problem of implementing environmental management accounting and strategy and product innovation during the covid 19 pandemic at the Dr. Radjiman Wediodiningrat Mental Hospital.The research used by the researcher is a qualitative research method. The subject of this research is the term respondent who is called the informant, Sub-Section of the Environmental Health Installation. The primary data source is interview, while the secondary data is in the form of documentation. Methods of collecting data by means of interviews and documentation. Qualitative data analysis according to Matthew B. Milles consists of 3 activities, namely: (1) data reduction, (2) data presentation, (3) conclusion drawing or verification.The purpose of this study was to determine the application of environmental management accounting and strategy and product innovation at the Dr. Radjiman Wediodiningrat Mental Hospital and looking for obstacles and solutions to these problems, so that it can be concluded as follows: (1) Application of environmental management accounting and strategies and product innovations during the covid 19 pandemic at Dr. Radjiman Wediodiningrat Mental Hospital has been implemented well, because the hospital has implemented environmental health and K3RS and implemented green hostpital. Supported by an assessment in PROPER, which is a program held in order to assess the performance of hospitals to control B3 waste, it has played a good role because the results of the proper assessment are in the blue category, meaning for companies that have made environmental management efforts required in accordance with the provisions or laws and regulations. - applicable invitation. (3) An internal obstacle at the Lawang Mental Hospital during the COVID-19 pandemic was that the performance of the medical and nursing directorates fluctuated in terms of performance productivity. The standard hostel facilities have not been met. Psychogeriatric research network is still not optimal, committed to excellent service has not reached the target. RSJ's income has not been able to finance all operational costs. (3) Troubleshooting Dr.Radjiman Wediodiningrat Mental Hospital during the covid 19 pandemic, by making efficiency in terms of service, efficiency in resources, work materials, launching telemedicine services, to reduce direct contact for the prevention of covid 19, and implementing a remuneration system for employees according to hospital conditions.Keywords: Environmental management accounting, strategy, innovation